Student outcomes in secondary physics flipped classrooms: An explanatory sequential mixed methods investigation - Pokhrel, Sunil; Wosti, Mukund; Subedi, Yam Prasad (Himalayan Physics, 2025)
This study investigates whether the flipped classroom approach enhances secondary-level students' learning achievement in a Secondary-level Physics course. It aimed to explore the effectiveness of the flipped model for students who have been primarily exposed to traditional lecture-based instruction throughout their schooling. An explanatory sequential mixed methods design was employed. Quantitative data were analyzed using ANCOVA to compare pre- and post-test results between experimental and control groups of urban and rural schools in Gandaki Province of Nepal. The quantitative analysis was followed by qualitative interviews to interpret the quantitative findings. The results indicated that the flipped classroom did not significantly improve student performance in the urban school, but showed a near-significant trend toward improvement in student performance in the rural school. Notably, in the urban school, students in the control group, who received traditional instruction, outperformed those in the flipped group. These findings suggest that the success of the flipped classroom approach is highly context and lived-experience-dependent and influenced by factors such as students’ readiness and access to digital resources.